2004
DOI: 10.1017/s0266467404001531
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a common palm, Oenocarpus mapora, on seedling establishment in a tropical moist forest in Panama

Abstract: Plants often modify microsite conditions important for seedling establishment. In tropical moist forest, advance regeneration in the form of shade-suppressed seedlings is a major component of regrowth in new gaps. Tree seedlings may be filtered by the composition and structure of the forest understorey. In a lowland forest in Central Panama, we examined light availability, Utter accumulation and the seedling community (abundance, diversity and composition) under and away from the canopies of a common subcanopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 61 publications
2
52
1
2
Order By: Relevance
“…Density/m 2 and the number of species/m 2 of the study's post-cotyledonous seedlings were not affected by litter depth. This result contrasts with the earlier report that seedling density was negatively correlated with litter depth under Oenocarpus (Farris-Lopez et al 2004). Litter would have its main effect on the earlier life stages of seedling emergence and small cotyledonous seedlings (Molofsky and Augspurger 1992;Vazquez-Yanes and Orozco-Segovia 1992).…”
Section: Do Individual Arborescent Palms Restrict Seedling Recruitment?contrasting
confidence: 89%
See 2 more Smart Citations
“…Density/m 2 and the number of species/m 2 of the study's post-cotyledonous seedlings were not affected by litter depth. This result contrasts with the earlier report that seedling density was negatively correlated with litter depth under Oenocarpus (Farris-Lopez et al 2004). Litter would have its main effect on the earlier life stages of seedling emergence and small cotyledonous seedlings (Molofsky and Augspurger 1992;Vazquez-Yanes and Orozco-Segovia 1992).…”
Section: Do Individual Arborescent Palms Restrict Seedling Recruitment?contrasting
confidence: 89%
“…Farris-Lopez et al (2004) demonstrated at BCI that Oenocarpus lowered survival, especially of small-seeded and shade-intolerant species. Therefore, at least at BCI, one species of arborescent palms may selectively favor certain groups of species during seedling establishment.…”
Section: Do Individual Arborescent Palms Restrict Seedling Recruitment?mentioning
confidence: 99%
See 1 more Smart Citation
“…Palm leaves and reproductive structures typically decompose slowly, forming a deep litter layer. Litter accumulation modifies microhabitat conditions and affects the recruitment of other plant species, as has been observed by Farris-Lopez et al (2004) for the palm Oenocarpus mapora, in Panama, and by Aguiar & Tabarelli (2010) for the palm Attalea oleifera, in Brazil, both of whom reported reductions in the abundance and richness of seedling species beneath palm crowns. Because R. oleracea is a tall palm with large, heavy leaves, negative effects on seedling recruitment beneath their crowns are also to be expected.…”
Section: Introductionmentioning
confidence: 74%
“…Palms (Arecaceae) are a group of plants common in tropical forests that can show morphological, phenological and genetic divergences among closely related species along resource gradients (Henderson et al 1995;Svenning 2001;Savolainen et al 2006). The lower montane forests examined here are a hotspot of diversity for understory palms, which comprise a major component of the understory and have the potential to alter regeneration patterns of woody seedlings (Farris-Lopez et al 2004;Harms et al 2004;Wang and Augspurger 2004). In a previous study, understory palm species composition was related to soil nutrients, particularly available nitrogen and cations (Andersen et al 2010a).…”
Section: Introductionmentioning
confidence: 98%